Valuing Product Attributes Using Single Market Data: A Comparison of Hedonic and Discrete Choice Approaches - Cropper, Maureen L.; Deck, Leland; Kishor, Nalin; McConnell, Kenneth E. (The Review of Economics and Statistics, 1993)
Maureen L. Cropper, Leland Deck, Nalin Kishor, Kenneth E. McConnell, Valuing Product Attributes Using Single Market Data: A Comparison of Hedonic and Discrete Choice Approaches, The Review of Economics and Statistics, Vol. 75, No. 2 (May, 1993), pp. 225-232